Correlation Between Systolic Deformation and Dyssynchrony Indices and the Grade of Left Ventricular Hypertrophy in Hypertensive Patients With a Preserved Systolic Ejection Fraction Undergoing Coronary Angiography, Based on Tissue Doppler Imaging. (1st January 2014) - Zoroufian, Arezoo; Razmi, Tannaz; Savandroomi, Zahra; Tokaldany, Masoumeh Lotfi; Sadeghian, Hakimeh; Sahebjam, Mohammad; Jalali, Arash
Abstract : Objectives: The purpose of this study was to investigate whether systolic mechanical dyssynchrony occurs in hypertensive patients with a normal coronary artery and a normal ejection fraction and its relationship with different degrees of left ventricular (LV) hypertrophy. Methods: A total of 125 angiographically normal coronary patients (42.4% male; mean age ± SD, 57.16 ± 8.26 years) with an ejection fraction greater than 50% were included, of which 84 were hypertensive and 41 normotensive. The hypertensive patients were categorized into 3 groups: no, mild, and moderate LV hypertrophy. Tissue Doppler and deformation imaging parameters were measured in the 6 LV basal segments at peak systole. Results: The frequency of dyssynchrony was 40.5% in the hypertensive patients compared to 19.5% in the control patients ( P = .020). Among the hypertensive patients, LV dyssynchrony was found in 5 patients (20%) with no hypertrophy, 20 (42.6%) with mild hypertrophy, and 9 (75%) with moderate hypertrophy. There was a moderate correlation between the grade of hypertrophy and septal‐lateral wall delay ( r = 0.497), 6–basal segment delay ( r = 0.454), overall strain ( r = 0.453), overall peak systolic velocity ( r = −0.430), and standard deviation of the time to peak systolic velocity in the basal segments ( r = 0.429). After adjustment for the LV end‐systolic diameter and body surface area, overall strain was the best correlate of the hypertrophy grade (odds ratio, 7.043; 95% confidence interval, 1.839–26.980; P = .0044). Conclusions: Among tissue Doppler and deformation indices, overall peak systolic strain was the strongest correlate of the LV hypertrophy grade. Therefore, in hypertensive patients with normal cardiac systolic function, a reduction in overall strain in the 6 basal LV segments may be a good indicator of progression of the LV hypertrophy grade and systolic dysfunction.